The Tafsīr Bi Al-Ma’ṡūr and Bi Al-Ra’yī in The Commentary of Abū Ja’far Al- Ṭaḥāwī : (Study in Aḥkām Al-Qur’ān Al-Karīm) - Moh. Abdul Kholiq Hasan (Islamic Religious Education Departement, 2021)
This study aims to investigate the tafsīr bi al-ma’ṡūr and bi al-ra’yī in the commentary of Abū Ja’far al-Ṭaḥāwī and its application methods. This study employed analytical descriptive method by employing content analysis theory towards the commentary of Aḥkām Al-Qur’ān Al-Karīm. The results suggest that Al-Ṭaḥāwī incorporates the tafsīr bi al-ma’ṡūr and bi al-ra’yī in his commentary although the general style is still the tafsīr bi al-ma’ṡūr. Al- Ṭaḥāwī has his own method in implementing the tafsīr bi al-ma’ṡūr and bi al-ra’yī. Among his methods in tafsīr bi al-ma’ṡūr is to compromise amongst narrations if it is possible, select and scientifically criticize the narrations, no comment, and avoid rejected Isrāiliyyāt narrations and false hadiṡ, unlike the commentary of al-Ṭabari. It is possible due to the differences of character between these two commentaries. Meanwhile, his method in tafsīr bi al-ra’yī is to reconcile both reasons and narrations in balance and equally important, avoid reasons outside their domain, interpret mutasyābihāt with muḥkamāt, and avoid wrong interpretation. Therefore, al-Ṭaḥāwī’s commentaries have been based on correct principles.